High triglyceride glucose-body mass index correlates with prehypertension and hypertension in east Asian populations: A population-based retrospective study - Chen, Lu; He, Linfeng; Zheng, Wenbin; Liu, Qiuying; Ren, Yifan; Kong, Wen; Zeng, Tianshu (Frontiers in Cardiovascular Medicine, 2023)
Background: There is compelling evidence demonstrating the relationship between triglyceride glucose-body mass index (TyG-BMI) and cardiovascular disease (CVD). However, data on the relationship between TyG-BMI and prehypertension (pre-HTN) or hypertension (HTN) remains scant. This study aimed to characterize the association between TyG-BMI and pre-HTN or HTN risk and assessed the power of TyG-BMI in predicting pre-HTN and HTN in Chinese and Japanese populations. Methods: A total of 214,493 participants were included in this study. The participants were divided into 5 groups according to the quintiles of TyG-BMI index at baseline (Q1, Q2, Q3 Q4 and Q5). Logistic regression analysis was then employed to evaluate the relationship between the TyG-BMI quintiles and pre-HTN or HTN. The results were presented as odds ratios (ORs) and 95% confidence intervals (CIs). Results: Our restricted cubic spline analysis demonstrated that TyG-BMI had a linear correlation with both pre-HTN and HTN. The multivariate logistic regression analysis suggested that TyG-BMI was independently correlated with pre-HTN [ORs and 95% CIs were 1.011 (1.011–1.012), 1.021 (1.02–1.023), 1.012 (1.012–1.012), respectively] and HTN [ORs and 95% CIs were 1.021 (1.02–1.021), 1.031 (1.028–1.033), 1.021 (1.02–1.021), respectively] in Chinese or Japanese individuals or both groups after adjusting for all variates. In addition, subgroup analyses showed that the relationship between TyG-BMI and pre-HTN or HTN was independent of age, sex, BMI, country, smoking and drinking status. In all the study populations, the areas under the TyG-BMI curve for predicting pre-HTN and HTN were 0.667 and 0.762, respectively, and thus the cutoff values were 189.7 and 193.7, respectively. Conclusion: Our analyses demonstrated that TyG-BMI independently correlates with both pre-HTN and HTN. Besides, TyG-BMI exhibited superior predictive power in predicting pre-HTN and HTN compared to TyG or BMI alone.